Experimentation on effect of particle ratio on hydrothermal performance of plate heat exchanger using hybrid nanofluid - Bhattad A.; Sarkar J.; Ghosh P. (My University, 2025)
To quantify the fostering in energetic and exergetic performances of counter flow corrugated plate heat exchanger, several experiments were conducted using Al2O3–MWCNT hybrid nanofluids as coolant. The Al2O3–MWCNT hybrid nanofluids with different nanoparticle volume ratios (5:0, 4:1, 3:2, 2:3, 1:4 and 0:5) and 0.01 v% concentration were used as a coolant for sub-ambient temperature application. Operating parameters which were varied are the coolant flow rate ranging from 2.0 to 4.0 lpm and coolant inlet temperature from 10 to 25 °C. Effects on heat transfer coefficient, heat transfer coefficient to pressure drop ratio, pump work, performance index, irreversibility and exergetic efficiency are investigated. Variation of Nusselt number with Reynolds number has also been studied for different nanoparticle volume ratios. Improvement up to 15.2% has been observed in the heat transfer coefficient for MWCNT (0:5) nanofluid with the negligible enhancement of 0.02% in the pump work and 2.96% enhancement in the performance index. Hydrothermal performance of nanofluids increases with increase in MWCNT ratio in particle mixture due to the negligible effect on pressure drop. No optimum ratio has been found within the studied mixture ratios of nanoparticles. © 2019 Elsevier Ltd